The Laffer curve and the growth maximizing tax rate analysis in achieving optimal economic growth - Yossinomita Yossinomita; Zulfanetti Zulfanetti (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
The Laffer curve and the growth maximizing tax rate (GMTR) can create optimal economic growth, which is very important in preparing the state revenue and expenditure budget and economic development. The implementation of economic development requires financing so that government expenditure growth often exceeds gross domestic product (GDP) growth. The size of the government is a measure of the ratio of total government spending to GDP. The amount of government spending is something that often happens in almost all countries in the world, especially in countries that are in the process of development. The problem is how the government can finance these increasing expenditures. There are two options available, namely on receipts from abroad in the form of foreign loans or on receipts from within the country. The tax sector is the determining sector that provides the largest contribution to domestic revenues. The size of this contribution requires that tax revenues continue to be increased, which can be seen from the tax ratio. The tax ratio is the ratio of total tax revenue to GDP. Several international multilevel studies have obtained in-depth analysis of this problem from the Laffer curve and GMTR approaches. This study convinces that the Laffer curve and GMTR can be applied to create the optimal economic growth.